La nueva ola de integración en Asia-Pacífico - Falck Reyes, Melba Eugenia; López Jiménez, José Jaime; Aceves Villalvazo, Santiago (México y la Cuenca del Pacífico, 2015)
Opinión Invitada y Presentación